Pengaruh Kualitas Pelayanan dan Citra Kampus Terhadap Word of Mouth dengan Kepuasan Mahasiswa sebagai Variabel Intervening (Studi pada Mahasiswa di Fakultas Teknologi dan Informasi pada Institut Bisnis dan Teknologi Indonesia (INSTIKI) Denpasar, Bali) - Sudianti, Ni Made; Bukhori, Mohammad; Rachmawati, Ike Kusdyah (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Competition in educational institutions is currently increasingly fierce, so student satisfaction and Word of mouth to attract prospective new students are of particular concern in order to achieve the development and existence of the institution. The aim of this research is to determine the direct and indirect influence of service quality and campus image on Word of mouth through student satisfaction as an intervening variable.The research was conducted on students of the Indonesian Institute of Business and Technology (INSTIKI) Denpasar, Bali. The sample was selected using a purposive sampling technique. The research instrument was a questionnaire distributed to 85 respondents from the class of 2021 (72 students from the IT Faculty and 13 students from the SK Faculty). The collected quantitative data was analyzed using SEM-PLS analysis using SmartPLS-4.0.9.8 software. The research results show that service quality and campus image have a direct and indirect positive and significant effect on Word of mouth through student satisfaction as an intervening variable. Meanwhile, student satisfaction acts as partial mediation.